Способы повышения учебной мотивации студентов-медиков при проведении самостоятельной работы по русскому языку как иностранному - Коновальчук, Н. А.; Коновальчук, Надія Олександрівна; Konovalchuk, N. A. (Київ: КІМ, 2016)
Мотивация является движущей силой учебного процесса, в частности такой его составляющей, как самостоятельной работы. При чем эффективность последней напрямую зависит от степени мотивации обучаемых. Поэтому целью данной статьи является рассмотрение и анализ методов, помогающих сохранить и повысить мотивацию во время самостоятельной работы студентов. Основными методами формирования и поддержания мотивации являются исследовательский и игровой методы. Выводы: таким образом, выбор формы и методов самостоятельной работы играет ведущую роль в формировании и поддержании степени мотивации. Выполнение однотипных заданий ведет к снижению уровня мотивации. Важно наряду с традиционным оцениванием и выставлением баллов использовать альтернативные методы оценки, такие как публично, вербальное и материальное поощрение. Мотивація є рушійною силою навчального процесу, зокрема такої його складової, як самостійна работа. Ще Е.Кант у своїх роботах торкався такого поняття, як мотивація. Проблемі мотивації студентів присвячували свої роботи такі дослідники-методисти, як І.О. Зимня, Н.Б. Нестерова, Є.П. Ільїн, А.Н. Леонтьєв. У наш час проблема мотивування студентів привертає увагу науковців. Про цю проблему пишуть Е.О. Мірошніченко, Л.М. Коптєва, М.М. Шабарова тощо. У наш самостійна робота посідає провідне місце серед інших видів робіт, адже знання, здобуті таким шляхом вважаються найміцнішими, також, щоб залишатися конкурентноспроможним, спеціаліст повинен вміти здобувати знання власними зусиллями. Але ефективність СР насамперед залежить від ступеня мотивації осіб, що навчаються. Всі ці чинники зумовлюють актуальність даної публікації. У статті розглядаються способи підтримання мотивації під час проведення СР по РКИ, розглядаються форми завдань, які, на думку автора, сприяють підвищенню мотивації та підтримці інтересу студентів. Метою цієї статті є розгляд і аналіз методів, що допомагають зберегти і підвищити мотивацію під час самостійної роботи студентів. Головними методами формування і підтримки мотивації є дослідницький і ігровий методи. Форми завдань, що сприяють підтримці мотивації та підвищенню інтересу до навчального предмету – творче дослідження, написання конспектів, рефератів, підготовка презентації та укладення кросвордів. Висновки: отже, вибір форми і методів самостійної роботи відіграє важливу роль у формуванні і підтримці ступеня мотивації. Виконання однотипних завдань приводить до зниження рівня мотивації. Важливо разом з традиційним оцінюванням і виставленням баллів використовувати альтернативні методи оцінки, такі як публічне, вербальне і материальне заохочення. The article is dedicated to the problems of maintaining and increasing educational motivation during independent work of students. E. Kant in his works touched motivation problems. I.O. Zimnya, N.B. Nesterova, E.P. Ilyin, A.N. Leontiev are dedicated their works to the problem of student’s motivation. Nowadays the problem of motivating of students attracted the attention of scientists. E.O. Miroshnichenko, L.M. Koptev, M.N. Shabarov and more are writing about this problem. In our independent work occupies a leading position among other works, because the knowledge acquired in this way are considered the strongest, too, to stay competitive, specialist should be able to acquire knowledge through their own efforts. Independent work is playing a leading role in modern training. Knowledges that students receive during independent work are the most long-lasting. We live in the information age. Every hour there are new information, and the old ones become irrelevant. Consequently, experts should be able to acquire knowledge on their own. The task of the teacher to teach students to learn independently. Only in this way they can be competitive and get a good job. Motivation is the driving force of the educational process, in particular a component of it, as an independent work. Withal the effectiveness of the independent work depends on the degree of motivation of the persons who is studing. Therefore, problem of students' motivation during independent work is relevant. This article discusses the problem of motivation of students during independent work on Russian as a foreign language, highlights the main form of tasks that, in our opinion, are able to raise motivation and to keep the interest of students to the task. Co of time in the process of learning motivation may change. in individuals with a high level of motivation motivation decreases and in persons with low levels of motivation there is a growing interest in the subject. A teacher should manage the process of change in motivation. Consequently the aim of this article is to review and analyze the methods that help maintain and increase motivation during independent work of students. The main methods of forming and maintaining motivation are research and game techniques. Forms of tasks that contribute to maintaining motivation and increase interest in subject what is studing - creative research, writing summaries, essays, preparing presentations and making of crosswords. Conclusion: Thus, the choice of form and methods of independent work has played a leading role in shaping and maintaining the degree of motivation. Performing similar tasks leads to a decrease in the motivation level. It is important, along with the traditional assessment and points to use alternative assessment methods, such as public, verbal and financial incentives.
Засоби підвищення навчальної мотивації студентів-медиків під час проведення самостійної роботи з російської мови як іноземної
Methods of increasing learning motivation of medical students during independent work in russian as a foreign language
Keywords: метод; мотив; учебная деятельность; учебная мотивация; самостоятельная работа; навчальна діяльність; навчальна мотивація; самостійна робота; independent work; learning motivation; method; motive; training activities